The Impact of Autonomic Dysreflexia on Blood Flow and Skin Response in Individuals with Spinal Cord Injury. (28th July 2008) - Ramella-Roman, J. C.; Hidler, J. M.
Abstract : Autonomic dysreflexia (AD) is an inappropriate response of the sympathetic nervous system that commonly occurs when individuals with spinal cord injury (SCI), at or above the sixth thoracic (T6) vertebra, are subjected to a noxious stimulus below the level of injury. An AD event can be put into motion by something as simple as an ingrown toenail or a full bladder, with symptoms ranging from headache, high blood pressure, and even stroke. We have characterized the onset of AD and resulting autonomic events in an individual with SCI using a fiberoptic-based probe. Two probes were located above and below the injury level, on the subjects forearm and thigh, respectively, and were connected to a dual channel spectrophotometer. Oxygen saturation was calculated using the reflectance spectra and an algorithm based on melanin and hemoglobin absorption. We noticed that during an AD event the amount of oxygen in the skin below the injury level dropped by as much as 40%, while above the injury level, skin oxygenation remained constant. In addition, we found that the level of skin perspiration below the level of injury increased significantly. We hypothesize that the combination of AD-related ischemia with pressure-related ischemia and increased perspiration places individuals with spinal cord injury level at T6 or above at an elevated risk for developing a pressure sore below the injury site.